1976
DOI: 10.1097/00000658-197609000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Treatment of Constrictive Fibrous Endocarditis

Abstract: Constrictive fibrous endocarditis is a pathological entity described by Loëffler in 1936. Its etiology is unknown. The clinical course is characterized by an evolution towards cardiac insufficiency leading rapidly to a fatal outcome. Moderen paraclinical investigations are necessary to assess the diagnostic. Caridac catheterization brings the proof of adiastole and angiogardiography reveals the shape of amputation of the ventricle with auriculoventricular regurgitation. The operative procedure consists of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Dubost is one of the first cardiac surgeons to describe the surgical technique for endomyocardial fibrosis, he showed that this disease occurs in the filling chamber of one or both ventricles, in the papillary muscles, in the chordae tendineae and in the valve leaflets. He also showed that it never involves the ventricular outflow tract neither the atrioventricular annulus nor the aortic orifice [ 5 ] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dubost is one of the first cardiac surgeons to describe the surgical technique for endomyocardial fibrosis, he showed that this disease occurs in the filling chamber of one or both ventricles, in the papillary muscles, in the chordae tendineae and in the valve leaflets. He also showed that it never involves the ventricular outflow tract neither the atrioventricular annulus nor the aortic orifice [ 5 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Starting the incision from the junction of valvular annulus and the fibrotic tissues then pursuing the dissection towards the ventricular apex where the adhesions are usually dense. Dubost also demonstrated that the thickened endocardium has to be completely excised for the reason to improve the diastolic function of the ventricle [ 5 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Löffler endocarditis was first described in 1936, as an acute form of fibrinous restrictive pericarditis. [ 3 ] Histologically, it is described as the migration of eosinophils into the myocardium with, tissue damage and fibrosis resulting from eosinophil degranulation. [ 4 ] Löffler endocarditis is a rare manifestation of hypereosinophilic syndrome.…”
Section: Introductionmentioning
confidence: 99%